2020
DOI: 10.3390/nu12113506
|View full text |Cite
|
Sign up to set email alerts
|

Blood SIRT1 Shows a Coherent Association with Leptin and Adiponectin in Relation to the Degree and Distribution of Adiposity: A Study in Obesity, Normal Weight and Anorexia Nervosa

Abstract: Sirtuin 1 (SIRT1) is a sensor of cell energy availability, and with leptin and adiponectin, it regulates metabolic homeostasis. Widely studied in tissues, SIRT1 is under evaluation as a plasmatic marker. We aimed at assessing whether circulating SIRT1 behaves consistently with leptin and adiponectin in conditions of deficiency, excess or normal fat content. Eighty subjects were evaluated: 27 with anorexia nervosa (AN), 26 normal-weight and 27 with obesity. Bloodstream SIRT1, leptin and adiponectin (ELISA), tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…As already described, we found the highest levels of SIRT1 in the underweight group of patients [ 10 , 21 ]. Accordingly, mice under calorie restriction with a significant loss of body weight show the upregulation of SIRT1 mRNA expression in bone associated with increased bone mass [ 16 ].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…As already described, we found the highest levels of SIRT1 in the underweight group of patients [ 10 , 21 ]. Accordingly, mice under calorie restriction with a significant loss of body weight show the upregulation of SIRT1 mRNA expression in bone associated with increased bone mass [ 16 ].…”
Section: Discussionsupporting
confidence: 77%
“…Some studies on sclerostin and bone reported this condition [ 23 , 57 , 58 , 59 ] and, in some cases, higher serum sclerostin was measured in women with normal BMD compared to women with osteoporosis [ 23 ]. However, the subtle relationship between excess fat, weight load and skeletal mass could be made more complex by the impaired adipokine production being secondary to increased fat mass [ 21 ]. Indeed, an increased risk of fragility fractures, despite a normal BMD, has been associated with secondary factors [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By evaluating the serum SIRT1 levels of 80 subjects, it was found that its content was closely and positively correlated with leptin and adiponectin. SIRT1 can be used as a plasma marker in clinical applications to evaluate energy metabolism and can be applied to weight management in obese people [14,15].…”
Section: Discussionmentioning
confidence: 99%